Using a modified ELECTRE method for an agricultural product recommendation service on a mobile device. (November 2016) - Lian, Jiunn-Woei; Ke, Chih-Kun
Graphical abstract: Highlights: Proposed an MCDM based approach which contributes to mobile commerce marketing. Identified five criteria to assist purchasing decisions regarding agricultural products. Perceived ease of use does not play a critical role regarding mobile app. Abstract: The present study integrates information system engineering and management methodologies to solve a real-life case problem. We develop an agricultural product recommendation service on a mobile platform, and then to understand users' acceptance to confirm that it can be used to solve the problem. For consumers, making the decision to purchase is complex and can be full of contradictions and conflicts. This raises the need to design a product recommendation service that uses multiple criteria to assist consumers. This study employs a modified Elimination Et Choice Translating Reality (ELECTRE) method determine a ranking order which will assist consumers in deciding which agricultural product to buy. Two major findings are proposed. First, we identified five criteria that assist consumers making buying decisions regarding agricultural products. Second, we find that when the system is established on a mobile platform, perceived ease of use does not play a critical role in user acceptance.